Chondromyxoid Fibroma of the Mandible in an Adolescent: Case Report and Microsurgical Reconstructive Option. (March 2015) - Khosla, Rohit K.; Nguyen, Christine; Messner, Anna H.; Lorenz, H. Peter
Chondromyxoid fibroma is a rare bony tumor that usually presents in the lower extremities of middle-aged adults. Involvement of the craniofacial skeleton is extremely rare. We present the unique case of an adolescent boy with a chondromyxoid fibroma of the mandible. The chondromyxoid fibroma in this patient recurred after initial treatment with curettage. We treated the recurrence with resection of the involved mandible and immediate reconstruction using a vascularized musculo-osseus seventh rib flap ("Eve procedure"). Despite complex reconstruction in adolescents due to skeletal immaturity, the rib flap has successfully grown with the patient up to 3 years postoperatively. Therefore, we believe the musculo-osseus rib flap is a feasible solution for complex ramus and condyle reconstruction of the growing mandible in the adolescent patient.